The Influence Of Stadium And Disease Complications On The Long Of Care Of Cervic Cancer Patients In Haji Adam Malik Center General Hospital, Medan - Ribka Panjaitan (Pena Cendekia Insani, 2022)
Every health service competes with each other to improve the quality of service in order to achieve the highest level of health. Until now, hospital services have become a vital institution in people's lives because they are the center of medical services. The role of a hospital must be able to provide quality services. One of the indicators of service quality assessment and to measure the level of hospital efficiency is determined by the length of stay or known as LOS (length of stay). This type of research is a quantitative research that uses an analytical survey method with a cross sectional approach. The population in this study were all medical record data of cervical cancer patients who were treated at the Haji Adam Malik General Hospital Medan as many as 86 Patient Medical Record Data and the sampling technique used the Total population technique, namely 86 medical record data. The results showed that of the 2 factor variables that affect the length of stay of cervical cancer patients after multiple linear regression tests were carried out, it was found that the disease stage variable had a p-value of 0.024 and the disease complication variable had a p-value of 0.043, The conclusion in this study is that , disease stage and disease complications have p-value <0.05, it can be seen that these two variables have an influence on the length of stay of cervical cancer patients at Haji Adam Malik General Hospital Medan.